Factors Affecting Decision on Environmental Modification according to Universal Design: A Case Study of a Private University - Sridara Tipian; Antika Sawadsri (My University, 2017)
The conventional belief of universal design objective is to benefits for few people with high cost of investment. It is, therefore, considered as unprofitable project, although Thai government has well developed laws according to the concept. A university is an organization which is affected by this concept, because it should be place where welcoming people of differences and opening opportunities for all to access education with equality. However, it is not easy for a private university to invest in building or modifying universal design environment due to surplus cost of implementation. The objectives of this research are to: 1) study factors in universal design implementation; and 2) analyze importance level of executives in deciding to invest in universal design implementation or modification. The research procedure and qualitative data collection was conducted with 59 informants by face-to-face semi-structured interview. The informants of this research comprised 56 physical users, and 3 executives and building managers. The research results show that factors affecting decision on environmental modification based on universal design principles in private universities are: 1) social structure, 2) understanding and recognition of human values; and 3) business image promotion. However, probable factors not facilitating universal design implementation in universities were: 1) investment budget, 2) architectural Aesthetic, and 3) utilization. Additionally, background of the interviewees is one of reinforcing factors for decision on universal design investment.
Keywords: Investment; Promotion (chess); Cultural Industries and Urban Development